Lise mezunu olup üniversiteye hazırlanan ergenlerin özerklik düzeyleri ile kaygı düzeyleri arasındaki ilişkinin incelenmesi - Lüle, Ali Rıza (My University, 2002)
Lise Mezunu Olup Üniversiteye Hazırlanan Gençlerin Özerklik Düzeyleri İle Kaygı Düzeyleri Arasındaki İlişkinin İncelenmesi konulu bu araştırmada şu soruların cevapları aranmıştır: 1. Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik düzeyleri; özerklik düzeylerinin cinsiyet, yaş, anne eğitim durumu, baba eğitim durumu, sosyo-kültürel düzey, üniversiteye giriş sayısı ve kardeş sayısına göre farklılaşma durumu; özerklik düzeylerinin lise mezuniyet notu ile ilişkisi nedir? 2. Lise mezunu olup üniversiteye hazırlanan gençlerin sürekli kaygı düzeyleri; sürekli kaygı düzeylerinin cinsiyet, yaş, anne eğitim durumu, baba eğitim durumu, sosyo-kültürel düzey, üniversiteye giriş sayısı ve kardeş sayısına göre farklılaşma durumu; sürekli kaygı düzeylerinin lise mezuniyet notu ile ilişkisi nedir? 3.Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik düzeyleri ile sürekli kaygı düzeyleri arasında ilişki var mıdır? İlişkisel tarama yaklaşımına uygun olarak düzenlenen araştırmanın evrenini İstanbul İli Kadıköy İlçesi'nde, üniversite giriş sınavlarına hazırlık dersleri veren dershanelerde öğrenim gören öğrencilerin tümü; örneklemi ise evrenden random yoluyla belirlenen 7 dershanede üniversiteye hazırlanan ve liseden mezun olmuş olan 202 kız ve 222 erkek öğrenci olmak üzere toplam 424 öğrenciden oluşmaktadır. Veri toplamak amacıyla üç araç kullanılmıştır: 1. Kişisel Bilgiler Formu 2. İlişkili Özerklik Ölçeği 3. Durumluk-Sürekli Kaygı Envanteri Verilerin çözümlenmesinde aşağıdaki istatistiksel analizler yapılmıştır: 1. Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik düzeyleri ve kaygı düzeylerini belirlemek için Aritmetik ortalamalar hesaplanmıştır. 2. Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik düzeyleri ve kaygı düzeylerinin çeşitli kişisel özelliklere göre farklılaşma durumunu belirlemek için t-testi ve varyans analizi hesaplanmıştır. 3. Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik düzeyleri ile kaygı düzeyleri arasındaki ilişkileri belirlemek için Pearson Çarpım Momentler Katsayısı hesaplanmıştır. Araştırmadan elde edilen bulgular şunlardır: 1. Lise mezunu olup üniversiteye hazırlanan gençlerin İlişkili Özerklik, Ayrışma, Kendine Güven, Davranışsal Özerklik, Tutum ve Değerlerde Özerklik, Çatışmasız Bağımsızlık ve İlişkililik düzeyleri ölçek ortalamasının üstünde, Duygusal Özerklik düzeyi ise ölçek ortalamasının altındadır. 2. Lise mezunu olup üniversiteye hazırlanan gençlerin İlişkili Özerklik, Kendine Güven, Davranışsal Özerklik, Tutum ve Değerlerde Özerklik, Çatışmasız Bağımsızlık ve İlişkililik düzeyleri cinsiyete göre farklılaşırken, Ayrışma ve Duygusal Özerklik düzeyleri cinsiyete göre farklılaşmamaktadır. 3. Lise mezunu olup üniversiteye hazırlanan gençlerin özerklik kavramı ve alt boyutlarının hiç biri yaşlara, anne ve babanın eğitim durumlarına ve üniversiteye giriş sayısına göre farklılaşmamaktadır. 4. Lise mezunu olup üniversiteye hazırlanan gençlerin Davranışsal Özerklik, Tutum ve Değerlerde Özerklik ve İlişkililik düzeyleri sosyo-kültürel durumlarına göre farklılaşırken, İlişkili Özerklik, Ayrışma, Kendine Güven, Duygusal Özerklik, Çatışmasız Bağımsızlık düzeyleri sosyo-kültürel durumlarına göre farklılaşmamaktadır. 5. Lise mezunu olup üniversiteye hazırlanan gençlerin Kendine Güven düzeyleri kardeş sayılarına göre farklılaşmakta; İlişkili Özerklik, Ayrışma, Davranışsal Özerklik, Duygusal Özerklik, Tutum ve Değerlerde Özerklik, Çatışmasız Bağımsızlık ve İlişkililik düzeyleri farklılaşmamaktadır. 6. Lise mezunu olup üniversiteye hazırlanan gençlerin sürekli kaygı düzeyleri ölçek ortalamasının altındadır. 7. Lise mezunu olup üniversiteye hazırlanan gençlerin sürekli kaygı düzeyleri cinsiyete, annelerinin eğitim durumuna ve kardeş sayılarına göre farklılaşmaktadır. 8. Lise mezunu olup üniversiteye hazırlanan gençlerin sürekli kaygı düzeyleri yaşlarına, babalarının eğitim durumlarına, sosyo-kültürel durumlarına ve üniversite sınavlarına giriş sayılarına göre farklılaşmamaktadır. 9. Lise mezunu olup üniversiteye hazırlanan gençlerin Sürekli Kaygı düzeyleri ile İlişkili Özerklik, Kendine Güven, Davranışsal Özerklik, Duygusal Özerklik, Tutum ve Değerlerde Özerklik, Çatışmasız Bağımsızlık ve İlişkililik boyutlarıyla ters yönlü ilişki vardır. Buna karşın Sürekli Kaygı düzeyleri ile Ayrışma düzeyi arasında ilişki yoktur. Genel anlamda Sürekli Kaygı düzeyi arttıkça özerklik düzeyi azalmakta, Sürekli Kaygı azaldıkça da özerklik düzeyi artmaktadır.

It is investigated answers of these questions in this research which is named as The study of the relation between the level of anxiety and the level of autonomy of young people those graduated high school and attending at preparation for the university entrance exam. 1. What is the level of autonomy of young people those graduated high school and attending at preparation for the university entrance exam, effects of sex, age, parents' educational level, socio-cultural level, number of taking the university entrance exam and number of brothers and sisters to the level of autonomy and the relation between the level of autonomy and high school graduation grade. 2. What is the continuous level of anxiety of young people those graduated high school and attending at preparation for the university entrance exam; effect of sex, age, parents' educational level, socio- cultural level, number of taking the university entrance exam and number of brothers and sisters to the continuous level of anxiety and the relationship between the continuous level of anxiety and high school graduation grade. 3. What is the relationship between the continuous level of anxiety and the level of autonomy of young people those graduated high school and attending at preparation for the university entrance exam. In accordance with the approach of related research, the universe of the research is all students those attending at dershanes which are preparing for the university entrance exam in Kadıköy/ İstanbul. The sample of the research is 202 female, 222 male and totally 424 students those graduated high school and are preparing the university entrance exam in 7 different dershanes which are selected randomly from the universe. 3 tools are used for collecting data: 1. Personal Information Form 2. Related Autonomy Scale 3. Situational-Continuous Anxiety Inventory It is done below statistical analysis for analyzing the data: 1. It is used the arithmetic average and the standard deviation to investigate the level of autonomy and the level of anxiety of young people those graduated high school and attending at preparation for the university entrance exam. 2. It is used the t-test and the variance analysis to investigate the differences in the level of autonomy and the continuous level of anxiety of young people those graduated high school and attending at preparation for the university entrance exam in respect to personal characteristics. 3. It is used Pearson Product Moment Coefficient to investigate the relationship between the level of autonomy and the level of anxiety of young people those graduated high school and attending at preparation for the university entrance exam and the relationship between those properties and high school success. These are the results obtained from the study: 1. Level of related autonomy, dissociation, self confidence, behavioral autonomy, autonomy in attitude and value, independence without conflict and relatedness of young people those graduated high school and attending at preparation for the university entrance exam is above the average but level of emotional autonomy is below the average. 2. Level of related autonomy, self confidence, behavioral autonomy, autonomy in attitude and value, independence without conflict and relatedness of young people those graduated high school and attending at preparation for the university entrance exam is changing in respect to sex but level of dissociation and emotional autonomy is not changing in respect to sex. 3. The concept of autonomy and sub dimensions of autonomy of young people those graduated high school and attending at preparation for the university entrance exam are not changing in respect to age, parents' educational level and number of taking the university entrance exam. 4. Level of behavioral autonomy, autonomy in attitude and value and relatedness of young people those graduated high school and attending at preparation for the university entrance exam are changing in respect to socio-cultural situation and level of related autonomy, dissociation, self confidence, emotional autonomy and independence without conflict is not changing in respect to socio-cultural situation. 5. Although there is a positive relationship between the level of dissociation of young people those graduated high school and attending at preparation for the university entrance exam and high school graduation grade, there is no relation with other dimensions of autonomy. 6. Level of self confidence of young people those graduated high school and attending at preparation for the university entrance exam is changing in respect to number of sisters and brothers but level of related autonomy, dissociation, behavioral autonomy, emotional autonomy, autonomy in attitude and value, independence without conflict and relatedness is not changing. 7. Level of continuous anxiety of young people those graduated high school and attending at preparation for the university entrance exam is below the average. 8. Level of continuous anxiety of young people those graduated high school and attending at preparation for the university entrance exam is changing in respect to sex, mother's educational level and number of sisters and brothers. 9. Level of continuous anxiety of young people those graduated high school and attending at preparation for the university entrance exam is not changing in respect to age, father's educational level, socio-cultural situation and number of taking the university entrance exam. 10. There is a positive relationship between the level of continuous anxiety of young people those graduated high school and attending at preparation for the university entrance exam and high school graduation grade. As anxiety increases, success increases and as anxiety decreases, success decreases. 11. There is a negative relationship between the level of continuous anxiety of young people those graduated high school and attending at preparation for the university entrance exam and related autonomy, self confidence, behavioral autonomy, emotional autonomy, autonomy in attitude and value, independence without conflict and relatedness. However, there is no relation between continuous anxiety level and dissociation level. Generally, as continuous anxiety level increases, autonomy level decreases and as continuous anxiety level decreases, autonomy level increases.
Keywords: Eğitim; Ergenlik Psikolojisi; Genç yetişkinler; Öğrenciler-lise; Sosyal guruplar; Toplum bilimleri; Yaş gurupları